NO2 sensor based on Al modified ZnO nanowires. (1st November 2021) - Ramgir, Niranjan S.; Goyal, C.P.; Goyal, Deepak; Patil, S.J.; Ikeda, H.; Ponnusamy, S.; Muthe, K.P.; Debnath, A.K.
Abstract: Hydrothermally grown ZnO nanowires (NWs) have been successfully modified by an ultrathin layer of Al resulting in an improved and highly selective NO2 sensor. ZnO NWs containing 1.8 at.% of Al (thickness - 5 nm) could reversibly detect NO2 in the range from 0.5 to 5 ppm. The sensor film showed a linear dependence for all the concentrations between 0.5 and 5 ppm. A sensor response of 6.2 towards 4 ppm of NO2 was reversibly achieved at 230 °C with swift response kinetics exhibiting response and recovery times of 18 and 65 s, respectively. Modification with Al causes the resistance of the sensor film to decrease with an analogous improvement in the sensor response. The observed decrease in sensor resistance agrees well with the findings of work function studies. Sensor film modified with Al showed 60 meV decreases in work function. NO2 being an oxidizing gas causes an increase in work function by 0.25 and 0.19 eV for pure and Al modified ZnO NW films, respectively. A gas sensing mechanism has been proposed based on gas sensing, Kelvin probe and X-ray photoelectron spectroscopy measurements. Graphical abstract: Image 1